Investor sentiment and stock returns in the Philippines - LOZARI, ENRIQUE (Archīum Ateneo, 2018)
This paper studied whether investor sentiment predicts individual stock returns in the Philippines, whether investor sentiment predicts stock returns of individual stocks differently, and whether investor sentiment affects difficult-to-arbitrage stocks more than others. It constructed a composite index based on the first principal component of investor sentiment proxies and used the index as a measure of investor sentiment in the Philippines. Using panel regression and multivariate regression analyses, the paper found that investor sentiment is a statistically significant leading indicator of stock returns and that this relationship is conditional on stock characteristics. It also found that difficult-to-arbitrage stocks are more affected by changes in investor sentiment. These findings indicate that the Philippine stock market is inefficient, implying the relevance of using fundamental and technical analysis in the Philippines. However, because the results could not establish the economic significance of investor sentiment on stock returns, this paper must not be construed as an endorsement of a trading strategy.